2014
DOI: 10.7567/jjap.53.053001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nb addition on glass-forming ability and magnetization behaviors of nanocomposite Nd–Fe–B–Nb strip flakes

Abstract: The influences of Niobium doping on the glass-forming ability (GFA) and magnetization properties of Nd–Fe–B–Nb alloys were investigated. It is found that the GFA of Nd–Fe–B–Nb alloys are improved by the Nb addition. It is also revealed that the GFA of the samples increases with the Nb content. Rapidly solidified Nd4.5Fe77− x Nb x B18.5 (x = 0, 0.25, 0.5, 0.75, 1) nanocomposite strip flakes were successfully prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…where It is well known that the total magnetic energy includes the demagnetization energy, magnetocrystalline anisotropy energy, and Zeeman energy. According to Equation (12)(13)(14), the demagnetization energy and magnetocrystalline anisotropy energy of Nd-Fe-B magnet at 298 K were calculated and compared with Zeeman energy. It can be found that Zeeman energy is 1.157 H 2 and 57.433H 2 times of demagnetizing field energy and magnetocrystalline anisotropy energy, respectively.…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…where It is well known that the total magnetic energy includes the demagnetization energy, magnetocrystalline anisotropy energy, and Zeeman energy. According to Equation (12)(13)(14), the demagnetization energy and magnetocrystalline anisotropy energy of Nd-Fe-B magnet at 298 K were calculated and compared with Zeeman energy. It can be found that Zeeman energy is 1.157 H 2 and 57.433H 2 times of demagnetizing field energy and magnetocrystalline anisotropy energy, respectively.…”
Section: Governing Equationsmentioning
confidence: 99%
“…How to optimize the microstructure is crucial to obtain outstanding-performance magnet. In the experiments, modifying the alloy composition, [12][13][14] applying magnetic field, [15][16][17][18][19][20] or controlling the cooling rate [21][22][23] are the most common methods to enhance magnetic properties. Usually, experimental research is a typical repetitive method, which consumes numerous human and material resources.…”
Section: Introductionmentioning
confidence: 99%
“…How to optimize the microstructure is critical for the successful synthesis of the ideal nanocomposite permanent materials with higher magnetic performance. At present, composition substitution or doping [11][12][13], increasing the cooling rate [14], applying external magnetic field [15][16][17] or thermal deformation [18][19][20][21][22] are the main methods to optimize the microstructure and improve the magnetic properties experimentally. Unfortunately, the optimization of composition or manufacture process based on the principle of empiricism can only provide a qualitative guidance, and plentiful repeated experiments and statistical analysis are still needed.…”
Section: Introductionmentioning
confidence: 99%